2021
DOI: 10.1007/s40299-021-00608-3
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Social Support, Psychological Capital, and Subjective Well-Being among College Students in the Context of Online Learning during the COVID-19 Pandemic

Abstract: This study examined the relationship between perceived social support and subjective well-being among college students in the context of online learning during the COVID-19 pandemic. 515 college students in China that participated in an online questionnaire investigation were selected as the research sample. The results showed that perceived social support was significantly and positively associated with life satisfaction and positive affect and was significantly and negatively related to negative affect among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 63 publications
6
39
0
1
Order By: Relevance
“…Besides, it was found in research among patients and relocating women that perceived social support was positively correlated to overall PsyCap and its components, hope, self-efficacy, resilience, and optimism ( Foote et al, 1990 ; Schönfeld et al, 2017 ; Sagi et al, 2021 ). Furthermore, evidence from the Chinese college students’ sample showed that PsyCap significantly mediated the relationships between perceived social support and subjective wellbeing ( Huang and Zhang, 2021 ). Peer support’s positive effect on enhancing self-efficacy and emotional adaptation was also evidenced ( Wang, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, it was found in research among patients and relocating women that perceived social support was positively correlated to overall PsyCap and its components, hope, self-efficacy, resilience, and optimism ( Foote et al, 1990 ; Schönfeld et al, 2017 ; Sagi et al, 2021 ). Furthermore, evidence from the Chinese college students’ sample showed that PsyCap significantly mediated the relationships between perceived social support and subjective wellbeing ( Huang and Zhang, 2021 ). Peer support’s positive effect on enhancing self-efficacy and emotional adaptation was also evidenced ( Wang, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…It uses the theory of self-determination and other empirical data and results of field research that investigate well-being and psychological variables associated with it, but in a more particular context, i.e., in the pandemic and of students. As shown by the results of the studies mentioned in the introductory part, in the pandemic, students encountered several difficulties in the transition and adaptation to online education (see for example, Yusuf and Jihan, 2020 ; Aftab et al, 2021 ; Huang and Zhang, 2021 ). We consider that some of these obstacles could be overcome with the help of some internal psychological variables, related to personality and regulation mechanisms of student motivation.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the context of the pandemic, the percentages could be reconsidered and reanalyzed, either by certain categories of participants (for example, by groups of students) or in certain specific situations, such as the transition to online education. This is because the rapid and widespread transition to online education during the COVID-19 pandemic disrupted intercollegiate relationships and student learning routines, led to less familiar instructional methods, and created technological barriers to online student learning ( Huang and Zhang, 2021 ). They do not have access to all tools and learning materials in the virtual environment or students simply did not participate in online courses ( Yusuf and Jihan, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In turn, poor academic performance has been found to affect the psychological well-being of students [ 105 , 106 , 107 ]. Moreover, Grubic et al [ 108 ] pointed out that the online learning might also cause more psychological stress for university students who have already experienced heightened levels of mental health problems and undermined psychological well-being during the COVID-19 pandemic [ 109 ].…”
Section: Discussionmentioning
confidence: 99%